Checklist of the family Acrididae Macleay, 1821 (Orthoptera) based on voucher specimens of major repositories in Sarawak - Farah Nabillah Abu Hasan Aidil Fitri,; Ratnawati Hazali,; Fatimah Abang,; Ahmad Irfan Abdul Razak,; Siti Nurlydia Sazali, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Acrididae is a family of insects consisting of the short-horned grasshoppers and locusts. Currently, knowledge on the faunistic composition of family Acrididae in Sarawak is still scarce. This study aimed to determine the species composition and to provide a current checklist of acridid fauna in Sarawak, using voucher specimens from Insect Reference Collection of Universiti Malaysia Sarawak (UIRC), and Research, Development and Innovation Division (RDID) of Forest Department Sarawak. A total of 925 specimens of acridid were examined, representing 5 subfamilies, 17 genera and 22 species. Subfamily Catantopinae was recorded with the highest number of species (8 genera; 10 species), followed by Oedipodinae (4 genera; 4 species), Cyrtacanthacridinae (2 genera; 3 species), Oxyinae (2 genera; 3 species), and Acridinae (1 genus; 2 species). The most abundant species was Traulia azureipennis followed by Valanga nigricornis. The least abundant species were Coloracris coerulescens, Coloracris sp., Craneopsis olivacea, Perakia borneensis and Phalaca waterstradti, which is represented by a singleton. This study serves as a fundamental data which will aid future taxonomic and ecological studies on Acrididae in Malaysia, particularly Sarawak.